2002
DOI: 10.1046/j.1462-2920.2002.00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of multiple extracytoplasmic function (ECF) sigma factors in the genome of Pseudomonas putida KT2440 and their counterparts in Pseudomonas aeruginosa PA01

Abstract: Pseudomonas putida KT2440 is highly successful in colonizing a variety habitats, including aquatic and edaphic niches. In accordance with this ability and with the need to adapt to changing environmental conditions, P. putida has developed sophisticated mechanisms of transcriptional regulation. We analysed, at the genome level, the repertoire of sigma factors in P. putida KT2440 and identified 24 sigma factors, 19 of which corresponded to the subfamily of extracytoplasmic function (ECF) sigma factors. We detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
87
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 62 publications
1
87
1
Order By: Relevance
“…The involvement of these regulatory systems in the expression of siderophore receptors provides an additional level of regulation, enabling P. aeruginosa to respond to the presence of siderophores in the environment as well as to levels of intracellular iron. This seems to be an important issue for environmental bacteria, as other species of Pseudomonas also contain large numbers of ECF sigma factors (37,56). In agreement with that, a genome-wide analysis of TonB-dependent receptors involved in regulatory pathways has indicated that these signaling systems are commonly found in several environmental bacteria but are only seldom present in dedicated human and animal pathogens (30).…”
Section: Discussionmentioning
confidence: 57%
“…The involvement of these regulatory systems in the expression of siderophore receptors provides an additional level of regulation, enabling P. aeruginosa to respond to the presence of siderophores in the environment as well as to levels of intracellular iron. This seems to be an important issue for environmental bacteria, as other species of Pseudomonas also contain large numbers of ECF sigma factors (37,56). In agreement with that, a genome-wide analysis of TonB-dependent receptors involved in regulatory pathways has indicated that these signaling systems are commonly found in several environmental bacteria but are only seldom present in dedicated human and animal pathogens (30).…”
Section: Discussionmentioning
confidence: 57%
“…This in turn correlates with the fact that many members of the TetR family are found among microbes with abundant extracytoplasmic function sigma factors (52,227,236,277,444).…”
Section: Identification Of Tetr Family Members In Dna and Protein Datmentioning
confidence: 88%
“…Table 3 shows that members of the TetR family were detected in 144 microbial genomes belonging to 80 genera and 113 species of gram-positive and ␣-, ␤-, and ␥-proteobacteria, cyanobacteria, and archaea, indicating wide taxonomic distribution. We have found that proteins of the TetR family are encoded both in chromosomes and in plasmids, and the mobility of the latter elements could be a source of the spread of genes in this family via horizontal transfer (147, 383), as is also the case with catabolic genes (77,160,236,410,426), antimicrobial resistance determinants (20,100,124), and 16S rRNA genes (347).…”
Section: Identification Of Tetr Family Members In Dna and Protein Datmentioning
confidence: 99%
“…Comparisons with genome sequences of other bacteria reveal homologs of FecIRA whose encoding genes are arranged in the same order as fecIRA of E. coli (7). Particularly abundant are fecIRA homologs in Pseudomonas aeruginosa (46), Pseudomonas putida (34), Nitrosomonas europaea, and Bacteroides thetaiotaomicron, for which 10, 11, 15, and 23 fecIRA gene clusters, respectively, are predicted (V. Braun and S. Mahren, unpublished results). The E. coli fecIRA type of transmembrane transcriptional control thus seems to represent a paradigm of a large number of similar transcriptional control devices in many gram-negative bacteria.…”
mentioning
confidence: 96%